2014
DOI: 10.4172/2157-7145.1000231
|View full text |Cite
|
Sign up to set email alerts
|

Age Estimation from Pulp/Tooth Area Ratio in Three Mandibular Teeth by Panoramic Radiographs: Study of an Egyptian Sample

Abstract: Subjects and Methods SamplesA total of 500 panoramic radiographs of Egyptian Subjects (262 males and 238 females), aged between 18 and 71 years were analyzed. These panoramic radiographs were undergone at the Oral Radiology Clinic, Faculty of Oral and Dental Medicine, Cairo University (Proline XC, Planmeca Oy -Helsinki, Finland). The exposure parameters were set according to the patient's age and size. The patient's identification number, sex, age and date of radiographic taking were recorded.The inclusion and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 28 publications
2
15
0
1
Order By: Relevance
“…As several studies have shown that gender does not influence the regression model, there has been no need for a sex-specific model. 7,13,[32][33][34][35] The present study supports this conclusion (p < 0.452), and we obtained a regression model applicable to both males and females. Thus, there is no need to know the sex of an individual prior to performing the age estimation procedure.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…As several studies have shown that gender does not influence the regression model, there has been no need for a sex-specific model. 7,13,[32][33][34][35] The present study supports this conclusion (p < 0.452), and we obtained a regression model applicable to both males and females. Thus, there is no need to know the sex of an individual prior to performing the age estimation procedure.…”
Section: Discussionsupporting
confidence: 85%
“…For this reason, the right or left teeth that were seen clearly and were appropriate for the measurement were selected in this study, which is similar to the method used in other studies. 6,7,13,33,34,36 One major limitation of this study is that the proposed regression model explained only 51.2% of total variation in age, which can be considered a moderate explanation. Despite this limitation, the regression model is still applicable and provides valuable information because it evaluates the validity of the regression model in an independent sample.…”
Section: Discussionmentioning
confidence: 88%
“…[ 1 ] Teeth are the most durable and reliable tool for forensic age estimation. [ 2 ] Various methods can be utilized for age estimation in children as well as in adults by the use of a tooth. [ 3 ] The measurement of secondary dentin deposition by dental radiographs is a simple and nondestructive method for age estimation.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have been performed to determine age by this method using canine,[ 2 4 5 ] first premolar, and second premolar either on intraoral periapical or panoramic radiographs. [ 2 ] Mathew et al . [ 6 ] developed an individual procedure of adult forensic age estimation by using mandibular first molar radiographs.…”
Section: Introductionmentioning
confidence: 99%
“…Examination and evaluation of dental records which are then presented in the interest of law for justice. [1] Identification is not an easy task in medicolegal cases in which answers by individuals are misleading or inaccurate to arrive at proper conclusion. [2] Digital forensics has replaced the traditional forensic investigations in terms of acquisition, analysis, and reporting of forensic evidence.…”
Section: Introductionmentioning
confidence: 99%